ACCULTURATION OF BETAWI DANCE AS A FORM OF SPREAD OF CHINESE CULTURE (SIPATMO DANCE STUDY) - Kusumaningtyas, Aryati Dewi; Pramutomo, RM. (Universitas Gadjah Mada, 2024)
The cultural component of the group itself is gradually assimilated into other cultures. The openness of a community will cause its culture to be influenced by the cultures of other communities, which can lead to cultural acculturation. Chinese culture is one of the cultural blends in the Jakarta area. The Sipatmo dance first appeared in the 17th century and advanced in the 18th century under the leadership of Memeh Karawang (originally Tan Gwat Niao). The purpose of this study is to determine the existence of the Sipatmo Betawi dance and the acculturation of the Betawi dance with Chinese culture. Therefore, descriptive research methods are used because this research aims to obtain answers related to people's responses, opinions, and perceptions. The results of these findings state that many residents do not know that the Sipatmo dance is a traditional Betawi dance that originates from there. Many of them do not know that the Sipatmo dance, which is also known as the Cokek dance, was originally a complementary dance performed during rituals at a temple. Even if this ownership is to be registered to clarify the category of regional culture, this depends on the art holders who are domiciled as citizens spread across the various administrative areas concerned.